Competing Processes Drive the Resistance of Soil Carbon to Alterations in Organic Inputs - Pierson, Derek; Peter-Contesse, Hayley; Bowden, Richard D.; Nadelhoffer, Knute; Kayhani, Kamron; Evans, Lucas; Lajtha, Kate (Frontiers in Environmental Science, 2021)
Protecting existing soil carbon (C) and harnessing the C sequestration potential of our soils requires an improved understanding of the processes through which soil organic matter accumulates in natural systems. Competing hypotheses exist regarding the dominant mechanisms for soil C stabilization. Many long-standing hypotheses revolve around an assumed positive relationship between the quantity of organic inputs and soil C accumulation, while recent hypotheses have shifted attention towards more complex controls of microbial processing and organo-mineral complexations. Here, we present our findings of soil response to twenty years of detrital manipulations in the wet, temperate forest of the H.J. Andrews Experimental Station. Annual additions of low quality (high C:N) wood litter to the soil led to an apparent positive, yet highly variable change in accumulation of soil C, while the addition of higher quality (low C:N) needle litter had no significant effect on soil C over the twenty year study. The observed contrast in soil C response between these two addition treatments demonstrates the important role of litter quality in soil C accumulation. Our detrital input reduction treatments, including cutting off live roots and aboveground removal of surface litter, led to relatively small effects on soil C concentrations after the twenty year study period. Far greater negative effects on soil C were observed for the removal of both aboveground litter and belowground root activity, which led to an estimated 20% decline in soil carbon stocks. The proportion of remaining soil C following these dramatic, long-term reductions in above and belowground detrital inputs suggests that the destabilization of C in these forest soils is not readily achieved over a few decades of reductions in detrital input, and may require far greater periods of time or further perturbations to the environment. Our diverse findings show that intermediate-term (10-20 years) forest disturbances giving rise to detrital changes in forest soils may alter soil C stocks depending on changes in detrital input quality and source. Further, our observed soil C responses to detrital manipulations strongly support recent soil C stabilization hypotheses which emphasize litter quality and mineral stabilization as relevant controls over forest soil C.